Pemanfaatan Dana Desa Dalam Pemberdayaan Ekonomi Masyarakat di Desa Sumberejo - Saraswati, Yudhistira (Fakultas Pertanian Universitas Jember, 2023)
Dana desa is an effort to realize equitable distribution of development between villages and cities through infrastructure development and community empowerment. The government has budgeted the use of Village Funds to boost the rural economy. The research approach is descriptive qualitative. Data collection by observation, in-depth interviews, and literature studies. The results of the study showed that dana desa was used to community economic empowerment. Empowerment is carried out through the development of BUMDesa. The group of activities consist of the development industry at agricultural sector, provision of venture capital assistance, and the creation of a creative village economy. These activities can create jobs opportunities, develop businesses, and encourage the economy of rural communities. The impact of dana desa is to reduce unemployment, reduce the rate of urbanization, social problems solving, improve welfare, and improve environmental quality.